TBoPS: A Tree Based Distributed Beacon Only Period Scheduling Mechanism for IEEE 802.15.4 - Nefzi, B.; Khan, Dawood; Ye-Qiong Song (2012 IEEE 8th International Conference on Distributed Computing in Sensor Systems, 2012)
IEEE 802.15.4 standard specifies a beacon-enabled mode which provides a synchronization environment using beacon transmissions. However, this mode is designed for single hop networks and its use in multi-hop networks is not straight-forward. The main challenges of using beacon-enabled mode in multi-hop networks are how to efficiently schedule beacon transmissions to avoid direct and indirect beacon collisions and how to make a schedule tolerant to the clock drifts due to the low cost components. In this paper, we present TBoPS, a novel technique for scheduling beacons in the cluster tree topology. TBoPS uses a dedicated period called beacon only period (BOP) to schedule beacons at the beginning of IEEE 802.15.4 super-frame. The advantages of TBoPS is that every beacon-enabled node selects a beacon schedule distributively during association. We analysed the robustness of TBoPS to clock drifts. We also show through simulations that all nodes in the network are synchronized and follow the same super frame structure.